Dark Triad in the Margins: Narcissism and Moral Erosion Among Marginal Migrant Entrepreneurs - Abdelaziz Abdalla Alowais; Abubakr Suliman (Administrative Sciences)
In informal economic contexts, migrant entrepreneurs have been extolled as highly resilient and adaptable. This study critically investigates the adverse psychological foundations inherent in such enterprises, focusing on how dark triad personality traits emerge in the leadership orientations of marginal migrant entrepreneurs. Following a qualitative ethnographic approach, this research engaged 10–15 migrant employees through participant observation, field notes, and semi-structured interviews in an informal economic context. Thematic analysis revealed five dominant patterns: narcissistic leadership with entitlement and emotional disrespect; Machiavellian behavior of manipulation and deception; psychopathic detachment in emotional callousness; absence of light triad actions such as empathy, humility, and selflessness; and moral disengagement through rationalizations such as “everyone does it” or system blame. Migrant business owners prefer to rationalize their exploitative acts as being necessary for economic survival, thus legitimizing immoral conduct and suppressing moral self-regulation. The findings indicate that marginality not only drives entrepreneurial innovation, but also has the potential to create exploitative inclinations that are institutionally and morally unchecked. Solving this issue requires not only mere psychological awareness, but also systematic reforms that foster ethical robustness and emotional sensitivity. This study ultimately asserts the need to reframe migrant entrepreneurship discourse, including both ethical and psychological accountability.